Woman As A Rational Being In Thomas Hardy's Far From The Madding Crowd (1874): A Feminist Approach - PRATIWI, RISKA ENDAH; , Dr. M. Thoyibi, M.S (2017)
Riska Endah Pratiwi/ A320130004. WOMAN AS A RATIONAL BEING IN THOMAS HARDY'S FAR FROM THE MADDING CROWD NOVEL (1874): A FEMINIST APPROACH. Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. March, 2017. The study is about a woman as a rational being reflected in Thomas Hardy's Far from the Madding Crowd (1874). The purpose of this study is to analyze the rationality of the major and minor women character based on the perspective of Feminist Theory about stereotypes of women. This study is descriptive qualitative study. The object of the study is Far from the Madding Crowd novel. There are two kinds of data source: Primary and Secondary data source. The Primary source is Far from the Madding Crowd (1874) novel by Thomas Hardy in English and Indonesian version. The secondary object is any references from books, journals, and articles related to the study. Technique of data collection is using Library Research and Note-taking method. Data are analyzed using descriptive qualitative method. The result of the research showed that the main character of woman in this novel, Bathsheba Everdene, fulfilled 4 criteria as a rational woman i.e. logical, reasonable, sane, and intelligent. Based on the analysis, Bathsheba is more rational than irrational, while the minor women characters are equal in both rational and irrational feature. Thomas Hardy wanted to criticize stereotypes of women in his era through the women character of his works including Far from the Madding Crowd.